2011
DOI: 10.3762/bjnano.2.89
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the critical current density in FeO-coated MgB2 thin films at high magnetic fields

Abstract: SummaryThe effect of depositing FeO nanoparticles with a diameter of 10 nm onto the surface of MgB2 thin films on the critical current density was studied in comparison with the case of uncoated MgB2 thin films. We calculated the superconducting critical current densities (J c) from the magnetization hysteresis (M–H) curves for both sets of samples and found that the J c value of FeO-coated films is higher at all fields and temperatures than the J c value for uncoated films, and that it decreases to ~105 A/cm2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…From the discovery of superconductivity in MgB2 till today, many studies have been reported on MgB2 in bulk, thin film, tape and wire forms (Erdem & Yanmaz, 2015;Surdu et al, 2011;Sun et al, 2019). These studies are generally related on the topics of MRI systems (Majoros et al, 2022), superconducting generators (Wen et al, 2019), power cables (Klöppel et al, 2021), magnetic field shielding (Gozzelino et al, 2019), and magnetic levitation force (Erdem et al, 2020).…”
Section: Introduction Girişmentioning
confidence: 99%
“…From the discovery of superconductivity in MgB2 till today, many studies have been reported on MgB2 in bulk, thin film, tape and wire forms (Erdem & Yanmaz, 2015;Surdu et al, 2011;Sun et al, 2019). These studies are generally related on the topics of MRI systems (Majoros et al, 2022), superconducting generators (Wen et al, 2019), power cables (Klöppel et al, 2021), magnetic field shielding (Gozzelino et al, 2019), and magnetic levitation force (Erdem et al, 2020).…”
Section: Introduction Girişmentioning
confidence: 99%
“…In order to design vortex-pinning landscapes, electron beam lithography is commonly used to fabricate arrays of holes [33,40] or arrays of magnetic dots/lines [30,34,36,39,41], whereas selective ion implantation [29,38,41] and insertion of structural defects [35,37,43] are other common pinning strategies. The use of a focused ion beam (FIB) for enhanced vortex pinning through local removal of the superconducting material has been explored as well [40,42,4648].…”
Section: Introductionmentioning
confidence: 99%
“…The external magnetic field very rapidly suppresses the critical current and destroys the superconductivity of magnesium diboride. This issue was successfully resolved by the introduction of self-assembled magnetic nanodots on the MgB 2 surface, which gives rise to a new hybrid material with the desired properties [ 2 ].…”
mentioning
confidence: 99%